2019
DOI: 10.1016/j.pec.2018.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Patient-clinician communication about sexual health in breast cancer: A mixed-methods analysis of clinic dialogue

Abstract: Objectives: Breast cancer patients' sexual health needs are frequently unmet. We examined the prevalence and content of communication about sexual health between breast cancer patients and clinicians. Methods: Female breast cancer patients being seen in oncology clinic follow-up had a clinic visit audio recorded and self-reported sexual problems after the visit. Transcripts were coded for sexual health communication; data were analyzed descriptively or using Chi-square tests. Results: We recorded 67 patients (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 36 publications
2
35
0
1
Order By: Relevance
“…For example, findings suggest that a sexual health communication intervention could have effects on clinicians' communication during routine clinical encounters, making the intervention directly relevant to practice. In addition, lack of time is a major perceived barrier to breast cancer clinicians in raising the topic of sexual concerns, and the findings of this study suggested that including discussions of sexual health did not significantly add time to the clinic visits. Whether longer discussions lead to better patient satisfaction or sexual health outcomes will need to be assessed in future research.…”
Section: Resultsmentioning
confidence: 75%
See 4 more Smart Citations
“…For example, findings suggest that a sexual health communication intervention could have effects on clinicians' communication during routine clinical encounters, making the intervention directly relevant to practice. In addition, lack of time is a major perceived barrier to breast cancer clinicians in raising the topic of sexual concerns, and the findings of this study suggested that including discussions of sexual health did not significantly add time to the clinic visits. Whether longer discussions lead to better patient satisfaction or sexual health outcomes will need to be assessed in future research.…”
Section: Resultsmentioning
confidence: 75%
“…Audio recordings of clinic encounters were transcribed and coded for sexual health communication using two levels of analysis. First, two coders determined the presence (y/n) of any sexual health communication, as described elsewhere . Second, dialogue relevant to sexual health was coded using a codebook developed for this study, with coding difficulties resolved through discussion.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations